Harmonizing Faith and Inclusion: Integrating Religious Values in Inclusive Education - Dian Arief Pradana; Mahfud Mahfud; Hary Priyanto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Inclusive education, an educational concept that promotes equality and participation of all individuals, is receiving increasing attention in a diverse global era. This article explores inclusive education from the perspective of religious literature, analyzing how the values and teachings of various religions can shape education that is inclusive, accepting, and respecting differences. Through library research methods, this article collects views from Islamic, Christian, Hindu, Buddhist, Jewish and traditional religious literature. The results of the study show that the concept of inclusive education can be found in universal values such as compassion, justice and brotherhood found in religious literature. These teachings offer a strong foundation for developing a learning environment that embraces diversity, builds student character, and promotes interfaith understanding. However, challenges in integrating religious values in educational practices are also found, including diverse interpretations and contextual adaptations. This article suggests steps towards implementing inclusive education based on religious values, including developing learning materials, training educators, collaborating with religious communities, and developing interfaith dialogue. Although complex, the application of this concept has the potential to shape a more inclusive and sustainable educational environment, building a society that values diversity and equality.